Land-use change and windstorms legacies drove the recolonization dynamics of laurel forests in Tenerife, Canary islands - Vicente Rozas; María A. García-López; José M. Olano; Gabriel Sangüesa-Barreda; Miguel García-Hidalgo; Susana Gómez-González; Roberto López-Rubio; José M. Fernández-Palacios; Ignacio García-González; Laura Lozano-López; Paula García-González; Ana I. García-Cervigón (Forest Ecosystems, 2023)
Laurel forests are quite relevant for biodiversity conservation and are among the island ecosystems most severely damaged by human activities. In the past, Canary laurel forests have been greatly altered by logging, livestock and agriculture. The remains of laurel forests are currently protected in the Canary Islands (Spain). However, we miss basic information needed for their restoration and adaptive management, such as tree longevity, growth potential and responsiveness to natural and anthropogenic disturbances. Using dendrochronological methods, we studied how forest dynamic is related to land-use change and windstorms in two well-preserved laurel forests on Tenerife Island. Wood cores were collected from over 80 trees per stand at three stands per forest. We used ring-width series to estimate tree ages and calculate annual basal area increments (BAI), cumulative diameter increases, and changes indicative of released and suppressed growth. Twelve tree species were found in all stands, with Laurus novocanariensis, Ilex canariensis and Morella faya being the most common species. Although some individuals were over 100 years old, 61.8%–88.9% of the trees per stand established between 1940 and 1970, coinciding with a post-war period of land abandonment, rural exodus and the onset of a tourism economy. Some trees have shown growth rates larger than 1 ​cm diameter per year and most species have had increasing BAI trends over the past decades. Strong growth releases occurred after windstorms at both sites, but the effects of windstorms were site-dependent, with the 1958 storm affecting mainly the eastern tip of the island (Anaga massif) and the 1991 storm the western tip (Teno massif). Given the great ability of laurel forest trees to establish after land use cessation and to increase growth after local disturbances such as windstorms, passive restoration may be sufficient to regenerate this habitat in currently degraded areas.